Adapting the revised self-leadership questionnaire to the Portuguese context - Marques-Quinteiro, P.; Curral, L.; Passos, A. M. (Social Indicators Research, 2012)
This study aimed to adapt the Revised Self-Leadership Questionnaire (RSLQ) (Houghton and Neck in J Manag Psychol 17(8):672–691, 2002) for the Portuguese population. 720 professionals, and university and post-graduate students participated in this study. The RSLQ factorial structure was accessed through exploratory and multi group confirmatory factor analysis. From the 9 sub dimensional and 34 items original scale, only 7 sub dimensions and 21 items were preserved. The model tested through cross-validation multigroup analysis proved to be totally invariant across the groups, suggesting good model fit.